2012
DOI: 10.2319/091311-593.1
|View full text |Cite
|
Sign up to set email alerts
|

Root proximity and cortical bone thickness effects on the success rate of orthodontic micro-implants using cone beam computed tomography

Abstract: When inserting OMIs, increasing the distance from the OMI to the root surface will significantly improve success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
2
37
0
4
Order By: Relevance
“…Although some researchers reported that there is no relationship between the cortical bone thickness and the stability of the mini screw, [40][41][42] others reported an opposing argument. 43,44 According to the results of the present study, there was no statistically significant difference among the groups. This outcome may be associated with providing adequate stability of the mini screws for maintaining stability until the end of the experiment.…”
Section: Discussionmentioning
confidence: 48%
“…Although some researchers reported that there is no relationship between the cortical bone thickness and the stability of the mini screw, [40][41][42] others reported an opposing argument. 43,44 According to the results of the present study, there was no statistically significant difference among the groups. This outcome may be associated with providing adequate stability of the mini screws for maintaining stability until the end of the experiment.…”
Section: Discussionmentioning
confidence: 48%
“…Some researchers found statistical significance and a higher success rate on the left side (5), as the same meaning found to be significant in this study, but on the opposite side (right). This side also exhibited greater failure rates in other studies, with (22) or without (1,4,15,16) statistically significant evidence to account for differences in the success rate. This result may be related to factors such as preferred side of mastication, access difficulties when placing the OMS or viewing the right or left side (7,10,22), different levels of oral hygiene among righties and lefties (23,24), and random statistical errors (5).…”
Section: Discussionmentioning
confidence: 67%
“…An orthodontic force of less than 200 g (cN) (4,8,(13)(14)(15) was applied immediately after placement of each OMS (5,8,11,13,14) by means of elastomeric chains (3,8,11,15). Analgesics were prescribed for the day of OMS placement.…”
Section: Methodsmentioning
confidence: 99%
“…Min et al (23) investigated the effects of root proximity on the success rate of a narrow screw (diameter 1.2-1.3 mm) and reported that the failure rate of the rootcontacting screw was about 70%. In contrast, of the 35 screws with root contact in the current study, 29 (about 83%) survived.…”
Section: Discussionmentioning
confidence: 99%